Molecular Changes In Cardiac Tissue As A New Marker To Predict Cardiac Dysfunction Induced By Radiotherapy - Ribeiro, Sónia; Simões, Ana Rita; Rocha, Filipe; Vala, Inês Sofia; Pinto, Ana Teresa; Ministro, Augusto; Poli, Esmeralda; Diegues, Isabel Maria; Pina, Filomena; Benadjaoud, Mohamed Amine; Flamant, Stephane; Tamarat, Radia; et al. (Frontiers in Oncology, 2022)
The contribution of radiotherapy, per se, in late cardiotoxicity remains controversial. To clarify its impact on the development of early cardiac dysfunction, we developed an experimental model in which rat’s hearts were exposed, in a fractionated plan, to clinically relevant doses of ionizing radiation for oncological patients that perform thoracic radiotherapy. Rat’s hearts were exposed to daily doses of 0.04, 0.3 and 1.2 Gy, for 23 days, achieving cumulative doses of 0.92, 6.9 and 27.6 Gy, respectively. We demonstrate that myocardial deformation, assessed by global longitudinal strain, was impaired (a relative percentage reduction of > 15% from baseline) in a dose-dependent manner, at 18 months. Moreover, by scanning electron microscopy, the microvascular density in the cardiac apex was significantly decreased exclusively at 27.6 Gy dosage. Prior to GLS impairment detection, several tools (qRT-PCR, mass spectrometry and western blot) were used to assess molecular changes in the cardiac tissue. The number/expression of several genes, proteins and KEGG pathways, related to inflammation, fibrosis and cardiac muscle contraction, were found to be differently expressed in the cardiac tissue, according to the cumulative dose. Subclinical cardiac dysfunction occurred in a dose-dependent manner as detected by molecular changes in cardiac tissue, a predictor of the severity of global longitudinal strain impairment. Moreover, there is no dose threshold below which no myocardial deformation impairment was detected. Our findings i) contribute to develop new markers and explore non-invasive magnetic resonance imaging to assess cardiac tissue changes as an early predictor of cardiac dysfunction; ii) should raise red flags, since there is no dose threshold below which no myocardial deformation impairment was detected and should be considered in the radiation-based imaging and -guided therapeutic cardiac procedures iii) highlight the need for personalized clinical approaches.